An interactive multi-scale integrated assessment of future regional water availability for agricultural irrigation in East Anglia and North West England. - Henriques, C.; Holman, Ian P.; Audsley, Eric; Pearn, Kerry R. (Springer Science Business Media, 2008)
A multi-scale approach has linked farm level decisions with regional water availability assessments that allow for environmental water needs and the competing demands for water. This is incorporated within a user-interactive software tool, enabling the impact of a range of variables to be easily examined. Climate change leads to increased potential irrigation demand in East Anglia and North West England. Under baseline socio-economic conditions, results suggest that such increased future water demands can be met in the North West, but in the drier East Anglian region are counter to the decreasing water availability under all climate scenarios. The decreasing availability is moderated or exacerbated according to the environmental priorities of the future socio-economic scenarios. Under economically focussed regional futures, water supply availability increases at the expense of the environment, despite high water demands. Under environmentally focussed futures, demand restrictions are needed due to the further decreased water availability as a consequence of the high environmental priority. Results show that the effectiveness of water pricing for reducing irrigation demand is also scenario-dependent. Where regional food production is important, irrigation demand is relatively price- insensitive and abstraction controls will be most effective, whereas in a global market-drive future, irrigation demand is shown to be price-sensitive.